2007
DOI: 10.1038/sj.gt.3303000
|View full text |Cite
|
Sign up to set email alerts
|

Rho-kinase as a novel gene therapeutic target in treatment of cold ischemia/reperfusion-induced acute lethal liver injury: effect on hepatocellular NADPH oxidase system

Abstract: In the transplant surgery, reactive oxygen species (ROS) from the reperfused tissue cause ischemia-reperfusion injury, resulting in the primary graft failure. We have recently reported that Rho-kinase, an effecter of the small GTPase Rho, plays an important role in the ROS production in the hyperacute phase of reperfusion; however, the sources and mechanisms of the ROS production remain to be elucidated. The aim of this study was to investigate the source of ROS production with a special reference to Rho-kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Pharmacological Nox inhibition with the unspecific apocynin attenuated necrotic and apoptotic cell death, O 2 -production, and lipid peroxidation in the murine and rat models of hepatic I/R (104,150). Moreover, apocynin and the Nox2-inhibitory peptide gp91ds-tat (41) prevented remote liver damage in a murine model of bilateral hind limb I/R (52).…”
Section: Gastrointestinal Tractmentioning
confidence: 98%
“…Pharmacological Nox inhibition with the unspecific apocynin attenuated necrotic and apoptotic cell death, O 2 -production, and lipid peroxidation in the murine and rat models of hepatic I/R (104,150). Moreover, apocynin and the Nox2-inhibitory peptide gp91ds-tat (41) prevented remote liver damage in a murine model of bilateral hind limb I/R (52).…”
Section: Gastrointestinal Tractmentioning
confidence: 98%
“…However, in the setting of ischemia-reperfusion and other processes related to critical illness, there is increased production of ROS through mitochondrial electron transport mechanisms, activation of the purine/xanthine oxidase system, and NADPH oxidase activation [9–11]. …”
Section: Participation Of Tlr2 and Tlr4 In Ischemia-reperfusion Injurymentioning
confidence: 99%
“…We and others have demonstrated that inhibition of superoxide production by xanthine oxidase, through allopurinol treatment, or from NADPH oxidase, as a result of blocking translocation to the membrane of the NADPH phox 47 subunit, protected mice from proinflammatory processes initiated by hemorrhage or ischemia-reperfusion injury [9–11, 27]. We have also shown that extracellular superoxide derived from xanthine oxidase is able to activate neutrophils and induce neutrophil-mediated proinflammatory responses through a TLR4-dependent mechanism [28].…”
Section: Participation Of Tlr2 and Tlr4 In Ischemia-reperfusion Injurymentioning
confidence: 99%
“…In non-phagocytic cells, ROS can be produced by the NADPH oxidase homolog Nox. Rho-kinase is associated with Nox, and Rho-kinase-dependent ROS production was found in I/R (65,66). Rho-kinase can also attenuate NO from endogenous nitric oxide synthase (eNOS), as well as regulate NF-kB through phosphorylation of IkB, and cause production of IL-6, monocyte chemoattractant protein (MCP-1), and migration inhibitory factor.…”
Section: Intracellular Pathways Of Cell Death and Survivalmentioning
confidence: 98%
“…ROS are produced in the hyperacute phase by hepatocytes, and later by KC (65). Sources of ROS include the mitochondrial electron transport chain, cyclooxygenase, nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, and xanthine oxidase (66).…”
Section: Intracellular Pathways Of Cell Death and Survivalmentioning
confidence: 99%